BETWEEN FISHING, MINING, AND SUCTION VESSEL: THE COMPROMISE OF TELUK LIMAU PEOPLE, WEST BANGKA, ON TIN MINING AGGRESSION - Ibrahim, .; Haryadi, Dwi; Wahyudin, Nanang (PEOPLE: International Journal of Social Sciences, 2019)
Teluk Limau Village is a tin-rich coastal village located in the northern tip of Bangka Island and administratively is a part of West Bangka Regency. With its natural wealth, the people of Teluk Limau have long been known as an area rich with marine resources as they are known as fishing villages. As the tin has begun permitted to be freely mined; however, Teluk Limau Village faces three major situations, namely the temptation to mine, the desire to continuously wrestle the marine world, and the lure of suction vessel companies to extract tin in its coastal areas. This paper used qualitative research method to explore information by determining snowball sampling. This study resulted in an attitude crossing among the people in which a half remained to be fisherman, some chose to become miners, and some other chose to compromise with the suction vessels existence that were visibly confronted with fishermen and community miners. After two major conflicts in opposing the existence of an offshore tin mining, the people finally decided to make peace, and even some of them decided to pursue the dual role of seasonal fishermen and seasonal miners. The study finally concluded that in situations where the benefits of all parties could be negotiated, in the end the dual attitude would not be a problem. Being agree to let them operate even disagree to each other's attitude has been the pragmatic choice of Teluk Limau Village people.